Solid waste composition from semi aerobic sanitary landfill/ Ram Sulaiman Ramli - Ramli, Ram Sulaiman (Faculty of Civil Engineering, 2006)
The successful planning for a waste management program is the availability of reliable information about the quantity and the type of material being generated. Municipal solid waste composition studies are essential to proper management of waste for a variety of reasons including a need to estimate materials recovery potential, to identify sources of component generation, to facilitate design of processing equipment, to estimate physical, chemical, and thermal properties of the wastes, and to maintain compliance with local, state, and national regulations. A study was conducted in Pulau Burung Sanitary Landfill which is locate at Seberang Perai Selatan, Pulau Pinang for the purpose of identifying waste composition (including chemical and physical characterization), as well as any daily variation. A methodology was developed for conducting a composition study for solid waste component. Hand sorting was used for classifying the collected wastes into the following categories: plastics, paper, metals, aluminium, leather, wood, textiles, rubbers, etc. Further analysis included ultimate analysis of combustible materials, energy content, methane and leachate production were also carried out. The result shows that the solid waste components dumped at the landfill are varies everyday, as a result of a change in consumption patterns. Two main waste categories were identified: food wastes and plastics, which represent 47% and plastic 21% of the total waste in Pulau Burung sanitary landfill. The moisture contents and leachate produced are influenced by weather and the characteristic of the solid waste while the energy produced is influenced by moisture which is low moisture will increased the energy to resource recovery for energy. The results of this study can be utilized by the regional solid waste authorities in order to establish an integrated waste treatment site, capable of fulfilling the regional waste management demands.